Librarian on the roof! : a true story - King, M. G. (Miriam Grace), 1968- (Albert Whitman, 2010)
This is the story of RoseAleta Laurell, who arrived in Lockhart, Texas, in 1989 to be the head of the Dr. Eugene Clark Library. The library was outdated, so she spent a week on the library roof to raise money and interest in the library, with special emphasis on a new children's section.